Pemanfaatan AI dalam Smart Farming untuk Mencapai SDGs 2 (Zero Hunger) di Indonesia - Ayuningtyas, Dilla Putri; Rositawati, Fina (FIA Unkris Press, 2025)
This study examines the role of Artificial Intelligence (AI) in the implementation of smart farming to support the achievement of Sustainable Development Goals (SDGs) point 2: Zero Hunger in Indonesia. Using a qualitative literature review approach, this research highlights AI’s contribution to improving agricultural production efficiency, optimizing resource management, and strengthening national food security. Various technologies such as automated irrigation systems, sensor-based pest and disease detection, accurate weather forecasting, and real-time data-driven food distribution are presented as potential solutions to reduce import dependency, increase crop yields, and stabilize food prices. AI also plays a vital role in supporting the four main pillars of food security: availability, utilization, accessibility, and stability. However, the implementation of AI cannot be effective without strong policy support from the government, adequate digital infrastructure, as well as continuous education and training for farmers to enable independent technology adoption. This study emphasizes that digital transformation through the integration of AI and the Internet of Things (IoT) is not merely a technical solution but also a strategic approach to building an agricultural system that is responsive to climate change, population growth, and food distribution challenges. Furthermore, this implementation is expected to open new economic opportunities in the agricultural sector through cost efficiency and increased value creation. In conclusion, AI-based smart farming becomes a driving force for modern agriculture that is inclusive, adaptive, and sustainable for Indonesia's future